The role of low molecular weight heparin in women with hereditary thrombophilia for good perinatal outcome - Vesna Sokol; Marina Ivanišević; Mislav Herman; Josip Đelmiš (Acta Clinica Croatica, 2016)
The aim of the study was to establish the importance of low molecular weight heparin (LMWH) treatment for good pregnancy outcome in patients with hereditary thrombophilia. This retrospective study included 70 patients with inherited thrombophilia who gave birth at Zagreb University Hospital Center in the period from January 2014 to January 2015. Fifty-seven women were treated and 13 women were not treated with LMWH. Perinatal outcome was significantly better in women with hereditary thrombophilia who were treated with heparin during pregnancy as compared with women without LMWH (p=0.006). Regardless of heparin therapy, patients with hereditary thrombophilia alone had a significantly better perinatal outcome as compared with women who, along with hereditary thrombophilia, had a history of habitual abortions (p=0.035) or intrauterine fetal death (p=0.033). Women treated with heparin had better perinatal outcome if they were without a history of recurrent or non-recurrent fetal loss (p=0.088). In the group without LMWH, perinatal outcome was significantly better in women with no history of habitual abortions as compared with women with recurrent miscarriages (p=0.047). Administration of LMWH is justified in women with hereditary thrombophilia and a history of adverse perinatal outcome.